Developing emotional intelligence and counseling self-efficacy in clinical pastoral education in healthcare settings: a multicenter pre-post study - Szilagyi, Csaba; Palmer, Patricia K.; Galchutt, Paul; Langstraat, Kristin; Fitchett, George (Frontiers in Medicine, 2025)
IntroductionEmotional intelligence (EI) and counseling self-efficacy (CSE) are essential qualities for healthcare chaplains who support individuals experiencing emotional and spiritual distress. Clinical Pastoral Education (CPE) serves as the primary clinical learning environment for developing EI and counseling skills within spiritual care practice. While limited research suggests CPE’s positive effects on personal and professional development, existing studies have methodological limitations. This study addressed these gaps by using validated instruments within a multicenter, pretest-posttest design. We investigated changes in EI and CSE during CPE, explored predictive factors, and examined the relationship between changes in EI and CSE among CPE students participating in their initial CPE unit (i.e., interns) and those in CPE residency programs (i.e., residents).MethodsWe used the Schutte Self-Report Emotional Intelligence Test and the Counselor Activity Self-Efficacy Scales to assess changes in EI and CSE. Students at ACPE-accredited CPE centers across the United States completed pre- and post-training surveys, along with mid-residency surveys for residents. Statistical analyses evaluated changes over time, compared interns and residents, and explored relationships between EI and CSE. Linear regression models identified significant predictors of pre-to-post changes.ResultsOur sample included 196 participants (mean age = 45.08 years; 47.4% female) from 29 accredited CPE centers, representing 9.6% of all centers across the United States. Most participants (95.9%) completed their training in healthcare settings. Significant increases in EI and CSE were observed among both CPE interns and residents (p < 0.001), with moderate to large effect sizes for EI and CSE. EI gains significantly predicted CSE improvements for both groups, with moderate correlations between EI and CSE changes. More CPE (residents vs. interns) facilitated greater increases in outcome variables, and longer program duration predicted greater EI gains for interns. The mode of delivery—in-person, hybrid, or online—did not significantly impact EI and CSE gains.ConclusionThis study demonstrates that participants’ EI and CSE significantly increased during their clinical education. The results show a strong relationship between EI and CSE development, suggesting that EI growth contributes to increased confidence in counseling abilities. The findings support CPE’s effectiveness in fostering essential skills for spiritual care providers, regardless of delivery modality or participant demographics.